COMMUNICATIVE FUNCTIONS OF IRONY IN VERBAL COMMUNICATION - Abduqodirova Madina Abduqayum qizi (World Scientific Research Journal, 2025)
Annotation. This article explores the communicative functions of irony in verbal communication. Irony is analyzed as a pragmatic and stylistic device that conveys implicit meanings, expresses attitudes, and facilitates indirect criticism or praise. The study highlights how irony enhances interpersonal interaction, reveals social norms, and reflects the speaker’s intention through contrast between literal and intended meaning. Different types of irony and their effects on the listener are also examined.